Evaluation of the essential oil of Melaleuca alternifolia antimicrobial activity of Cheel on Candida albicans, in the root canal in vitro and as temporary dressing - Reis Storto, Viviane (2015)
Candida albicans can be present in pulpal pathologies, in the pulp treatment and after the filling of the root canals, is responsible for recurrence of the infection leading to the need for root channel retreatment, since the auxiliary chemicals do not act on some samples of these yeasts. New research with products of the vegetable origin like essential oils aimed at the effective treatment of these infections. The essential oil of Melaleuca alternifolia Cheel is popularly known for its antimicrobial activity. The aim of this work was to study the activity of the essential oil of M. alternifolia Cheel on C. albicans, in vitro, inside the root canal system in vitro and as a dressing in subinibitory doses and evaluate exoenzyme production proteinase and phospholipase and phenotypic characteristics (fringes). A total of 64 strains of C. albicans and two standard samples being a C. albicans ATCC 90028 one C. albicans ICB 12 A were used in thes study. To evaluate in vitro antifungal activity of essential oil of M. alternifolia used the technique of microdilution in base two in RPMI 1640 with pure oil plus Tween 20 and Tween 80 at 0.02% as surfactant and 1% DMSO as a solvent. In vitro inside teeth contaminated with C. albicans, essential oil of M. alternifolia in RPMI 1640 and 0.02% Tween 20 as medicament. In vivo as dressing in 10 patients with necrotic pulp essential oil of M. alternifolia, 20% v / v ...